DESIGN AND DEVELOPMENT OF DIGITAL LEARNING RESOURCES ON PROBABILITY FOR SENIOR HIGH SCHOOL STUDENTS USING FLIP PDF PROFESSIONAL - Ika Meika; Fitriyani Yani; Deni Pratidiana (Math Educa Journal, 2025)
This research is conducted to design and developing digital teaching materials on the subject of opportunities for class XII SMA by utilizing the Flip PDF Professional application, as well as assessing as to examine their validity and practicality. The research applies a Design-Based Research (DBR) methodology using Plomp’s model, which includes three phases: initial research, expert evaluation with one-to-one sessions, and small-group plus field testing. Data were gathered using expert validation sheets and questionnaires for students. The results demonstrated that the developed digital instructional material obtained validity percentages of 95% from content experts, and 93.3% each from media and language experts. Student evaluations (one-to-one) yielded an average score of 93.9%, resulting in an overall average of 93.85%, categorized as highly valid. In the field testing phase, the teaching material achieved an average percentage of 83.51% in the indicators of ease of use, presentation, readability, and time efficiency, which falls into the "feasible" category. These findings indicate that the digital teaching material supported by Flip PDF Professional is suitable for use as an engaging, interactive, and student-centered alternative in mathematics learning.